High-sensitivity troponin I predicts major cardiovascular events after noncardiac surgery. (25th November 2020) - Borges, F.K; Duceppe, E; Heels-Ansdell, D; Ofori, S.N; Marcucci, M; Kavsak, P.A; Pettit, S; Spence, J; Belley-Cote, E; Lemanach, Y; McGillion, M; Whitlock, R; et al.
Abstract: Background: Myocardial injury after noncardiac surgery (MINS) is common and is associated with postoperative major cardiac events and 30-day mortality. We have previously established the diagnostic criteria for MINS with the 4th-generation cardiac troponin T assay (TnT) and 5th-generation high-sensitivity TnT assay (hsTnT) based on prognostically relevant thresholds. Little is known about diagnostic criteria for MINS using the high-sensitivity troponin I (hsTnI) assay. Purpose: To determine hsTnI thresholds associated with 30-day major cardiac events and death after noncardiac surgery. Methods: We performed a nested prospective biobank cohort study of 4545 patients from the VISION Study. Patients were aged ≥45 years and underwent in-patient noncardiac surgery under regional or general anesthesia. Patients had samples collected and frozen preoperatively, and on postoperative days 1, 2 and 3. We measured hsTnI on thawed preoperative and postoperative samples. We used iterative Cox proportional hazard models to determine peak postoperative hsTnI thresholds independently associated with major cardiac events (i.e., composite of death, non-fatal cardiac arrest, congestive heart failure within 30 days and non-fatal myocardial infarction from postoperative days 4–30). Results: Major cardiac events occurred in 89/4545 (2.0%) patients. Peak hsTnI values of <75 ng/L, 75 ng/L to <1000 ng/L, and ≥1000 ng/L were associated with an incidence of major cardiac events of 1.2% (95% CI 0.9–1.6), 7.1% (95% CI 4.8–10.5) and 25.9% (95% CI 16.3–38.4), respectively. Compared to peak hsTnI <75 ng/L (reference), hsTnI values 75 ng/L to <1000 ng/L and ≥1000 ng/L were associated with adjusted hazard ratios (aHR) of 4.53 (95% CI 2.75–7.48) and 16.17 (95% CI 8.70–30.07), respectively. No change from preoperative hsTnI to peak postoperative hsTnI significantly improved the model when included on top of the identified thresholds. Incidence of major cardiac events was 31/343 (9%) in patients with postoperative peak hsTnI ≥75 ng/L versus 52/4178 (1%) in patients with postoperative peak hsTnI <75 ng/L (aHR 5.76; 95% CI 3.64–9.11). A postoperative peak hsTnI ≥75 ng/L was associated with increased risk of major cardiac events either in the presence (aHR 9.35; 95% CI 5.28–16.55) or absence (aHR 3.99; 95% CI 2.19–7.25) of clinical features of myocardial injury (e.g., chest pain, ischemic electrocardiography changes). Conclusion: A hsTnI elevation within the first 3 days after noncardiac surgery independently predicts major cardiac events at 30 days. A peak postoperative hsTnI ≥75 ng/L was associated with a 6-fold increase in the risk of subsequent major cardiac events at 30 days as compared to peak postoperative hsTnI<75 ng/L. This hsTnI threshold can be used to diagnose MINS. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Siemens Healthcare Diagnostics Inc. Canadian Institutes of Health Research